Environmental Attitude as a Mediator Between Consumer Innovativeness and Purchase Intention: An Empirical Investigation - Diah Hermawati (Journal of Management and Business Innovation, 2025)
This study examines the direct and indirect effects of consumer innovativeness on purchase intention. As a key contribution, the study incorporates environmental attitude as a mediating variable. A quantitative approach was employed, using an online questionnaire distributed to 160 respondents. The sampling technique applied was purposive sampling, targeting university students across Indonesia who met predefined criteria. Prior to hypothesis testing, data quality was assessed through validity and reliability tests. Structural equation modeling using SmartPLS was then utilized to evaluate the proposed hypotheses. The findings indicate that consumer innovativeness has a significant direct effect on purchase intention, suggesting that higher levels of innovativeness correspond to stronger purchase intentions. Moreover, environmental attitude is confirmed to mediate the relationship between consumer innovativeness and purchase intention. Future studies are recommended to incorporate moderating variables such as gender and age to yield deeper insights.